The Romanticism Movement in Arabic Literature - Dyah Adila Perdana; Tatik Mariyatut Tasnimah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
This article discusses the Romanticism that developed rapidly in Arabic literature. The purpose of this study is to discuss the history of Romanticism and its influence in Arabic Literature and its Romanticist characters. This study used descriptive qualitative method. The technique used is the listening and note-taking technique. The results obtained are 1) The history of Romanticism in Arabic literature was influenced by the west when Napoleon set foot on Arab lands in the 20th century and also as a critique of the Classical School. 2) The influence of Romanticism in Arabic Literature is the emergence of several literary groups such as the Mahjar Group, Diwan School, Apollo School and Ushbah Al-Asyrah (Ten Leagues). Apart from the association of literary groups, it was also influenced by the renewal of magazines and newspapers in the Arab world after Napoleon's arrival in Egypt. 3) One of the figures of Arab Romanticism, namely Khalil Mutran, Khalil Gibran and Ahmad Zaki Abu Syadi.